Properties of LPG Carbon Residue Prepared with the Activated Method at High Temperature - Guang-Qiu, Lu; Min, Yang; Gui-Quan, Feng; Hong-Bin, Wang (Asian Journal of Chemistry, 2011)
In this paper, activated carbon is prepared form the carbon residue of Lugi pressurized gasifier slag (LPG carbon residues) with KOH solution as activating agent with the chemically activated method at high temperature. This work reports the influence of activation temperature, activation time and the mass ratio of raw materials and activating agent on the properties of activated carbon. The experimental results show that the great specifc surface area and interspace of activated carbon prepared from the coal residue has a great property of adsoption of phenol.